PENERAPAN METODE KELOMPOK INVESTIGASI DALAM PEMBELAJARAN MENULIS RESENSI NOVEL - Intan Aeni; Rosi Gasanti; Asih Wiarsih (Education First Journal, 2026)
Indonesian language learning is a process in teaching language skills that has an important role in it, by mastering language skills. One of them is writing skills, as for students' problems in writing, namely the lack of students' ability to express ideas, and the lack of students' understanding of linguistic rules is also an influencing factor. In addition, in writing there are other problems such as the inappropriate use of methods or strategies that result in learning activities tending to be boring and making students less able to be more active in the learning process. The purpose of this study was to see how learning to write novel reviews for class XI MIPA 1 MAN 4 Tasikmalaya students before and after applying the investigation group method and to find out the results of applying the investigation group method in learning to write novel reviews for class XI MIPA 1 MAN 4 Tasikmalaya students. A quantitative approach with an experimental model through a one group pretest-posttest design was used in this study. The sampling technique used was a purposive sampling technique, while the sample taken was 22 students of class XI MIPA 1. The data collection technique in this study was through tests and documentation. The data analysis technique used a paired samples t-test and prerequisite tests, namely the normality test and homogeneity test on SPSS 26.0. The results of this study indicate that there are significant results with the application of the investigation group method in learning to write novel reviews and are proven by the value of the results of writing reviews of class XI MIPA 1 students after applying the investigation group method with an average result value of 92.05 from the previous value of 66.5